Structural comparisons of meptazinol with opioid analgesics - LI Wei; HAO Jing-lai; TANG Yun; CHEN Yan; QIU Zhui-bai (Acta Pharmacologica Sinica; Vol 26, No 3 (March 2005): Acta Pharmacologica Sinica, 2016)
Aim: To investigate the mechanism of action of a potent analgesic, (±)-meptazinol. Methods: The structures of meptazinol enantiomers were compared with opioid pharmacophore and tramadol. Results: Neither enantiomer of meptazinol fitted any patterns among the opioid pharmacophore and tramadol, although they did share some structural and pharmacological similarities. However, the structure superpositions implied that both enantiomers of meptazinol might share some similar analgesic mechanisms with typical opiate analgesics. Conclusion: Meptazinol should have a different mechanism of action to known analgesics, which would be helpful in further investigations of meptazinol in the search for non-addictive analgesics.